2004
DOI: 10.1111/j.1365-2621.2004.tb13365.x
|View full text |Cite
|
Sign up to set email alerts
|

Water Solubility, Mechanical, Barrier, and Thermal Properties of Cross‐linked Whey Protein Isolate‐based Films

Abstract: Water solubility, thermal properties, tensile strength, percent elongation, oxygen permeability (OP), and watervapor permeability (WVP) of cross-linked glycerol plasticized whey protein isolate films were studied to determine the effect of cross-linkers (glutaraldehyde, formaldehyde, dialdehyde starch, carbonyldiimidazole, and UV irradiation) on film properties. With the exception of UV treatment, solubility of the films decreased (P < 0.05) upon treatment of the film-forming solutions with chemical cross-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 29 publications
9
73
2
Order By: Relevance
“…The presence of a high amount of cross-linkers in the film-forming solutions has been reported to lower the solubility (Ustunol and Mert 2004). Ealier, Galietta et al (1998) reported decreased solubility of glycerol-plasticized films cross-linked with formaldehyde, and they suggested that the decrease was due to of the formation of covalent bonds.…”
Section: Water Solubility and Swelling Propertiesmentioning
confidence: 99%
“…The presence of a high amount of cross-linkers in the film-forming solutions has been reported to lower the solubility (Ustunol and Mert 2004). Ealier, Galietta et al (1998) reported decreased solubility of glycerol-plasticized films cross-linked with formaldehyde, and they suggested that the decrease was due to of the formation of covalent bonds.…”
Section: Water Solubility and Swelling Propertiesmentioning
confidence: 99%
“…Although there are some reports on using DAS as cross-linking agent for various proteins, such as soy protein isolate [26,27], collagen [28], corn zein [29], flour starch-protein [30], and whey protein [31], to the best of our knowledge there are very few studies on keratin materials cross-linked with DAS. We previously reported that the mechanical properties, thermal stability, and water vapor barrier property of FK/PVA blended films could be improved by DAS-induced cross-linking [32].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors working with different lipids have previously reported improvements in film properties after the lipids were incorporated into the films (Teixeira et al 2014;Monedero et al 2010). Although several studies have been carried in cross-linking of proteins using various cross-linkers such as chemical agents, it is as observed by Ustunol and Mert (2004) difficult to compare results from different studies because of different experimental conditions.…”
Section: Introductionmentioning
confidence: 52%
“…It was observed (data not shown) that the fraction less than 180 Da which covered the gallic acid had the highest concentration after gallic acid treatment (56 % for the gallic acid treated film solution against 22 % for the control) suggesting that gallic acid was retained and considering the hydrophilic nature of gallic acid, this might probably be the reason for the increased solubility from the presumed trapped gallic acid in the film matrix. However, some authors working with chemical agents such as formaldehyde reported a reduction in solubility after cross linking (Ustunol and Mert 2004) suggesting probably that the chemical composition and properties of the chemical cross linkers apart from their action in formation of covalent bonds through cross-linking can also influence other film properties in different ways. The incorporation of oleic acid in the zein films significantly reduced solubility and the trend was that the increased oleic acid concentration resulted in further reduction in solubility and this was attributed to the hydrophobic nature of oleic acid.…”
Section: Effect Of Gallic Acid On Thickness Moisture Content and Solmentioning
confidence: 99%